LANGUAGE ATTITUDE OF MANDAILINGNESE TEENAGERS IN DESA SIDOJADI KECAMATAN BUKIT MALINTANG KABUPATEN MANDAILING NATAL - Leli Fitri Hasibuan; Busmin Gurning; Rahmad Husein (LINGUISTIK TERAPAN, 2019)
This study deals with language attitude of Mandailingnese teenagers in Desa Sidojadi Kecamatan Bukit Malintang Kabupaten Mandailing Natal. It was aimed to investigate the language attitude of Mandailingnese teenagers in Desa Sidojadi Kecamatan Bukit Malintang Kabupaten Mandailing Natal, realization of language attitude and the reasons why they have the language attitude such the way it is. This study used qualitative method then the design was descriptive qualitative research. The data of this study were the utterances of Mandailingnese teenagers in Desa Sidojadi Kecamatan Bukit Malintang Kabupaten Mandailing Natal. The source of data of this study was eleven Mandailingnese teenagers who lived in Desa Sidojadi Kecamatan Bukit Malintang Kabupaten Mandailing Natal. Observation and Interview were used to obtain the data. The data were analyzed by using Miles, Huberman, and Saldana’s Interactive Model (2014). Based on the data analysis, the Mandailingnese teenagers in Desa Sidojadi Kecamatan Bukit Malintang Kabupaten Mandailing Natal tend to be positive, they realized their language attitude in three domain, they are family domain, friendship domain, and religion domain. They have positive language attitude because they are loyal  to use Mandailing language, they feel proud to have Mandailing language, and they have awareness of language norm.Keywords: Language attitude, descriptive qualitative research, Miles, Huberman and Saldana’s Interactive Model